Synthesis of Chemically Modified Cellulose Bearing Schiff Base with Chelating Groups for Removal of Heavy Metals from Aqueous Solution: Characterization and Application of Chemically Modified Cellulose for Heavy Metal Removal from Aqueous Solution (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Chemically modified cellulose bearing metal binding sites were synthesised and characterised by Fourier transform infrared and solid state 13C-nuclear magnetic resonance (NMR) analysis, such as Schiff base and carboxylic acid groups. Due to its metal ion absorption potential for Cu (II) and Pb(II) ions from aqueous solution, the chemically modified cellulose (Cell-PA) adsorbent was examined. Under optimal conditions, kinetic and isothermal studies were carried out. The experimental data matches well with pseudo-second-order kinetics and Langmuir isotherm. Thermodynamic tests along with efficiency studies of adsorption regeneration were also conducted. The adsorbent (Cell-PA) demonstrates a high propensity for the removal of metal ions Cu (II) and Pb(II) and demonstrates antibacterial activity against selected microorganisms. The most vital element of natural resources is water, which is essential for the survival of all living species, including human beings, food production, and agricultural, recreational and industrial activities. Economic development, patterns and the climate are all highly impacted by the quality and availability of water. Water quality is altered by anthropogenic activities and is decreasing as urbanisation, waste disposal, climate change, population growth, industrial development and other factors increase.